Anything to Stay Alive: The Challenges of a Campaign for an Experimental Drug. Issue 1 (15th May 2015) - Geffen, Nathan
Abstract: Drug‐resistant tuberculosis (TB) has a high mortality rate. Most medicines used to treat it are poorly tested and have terrible side effects. Activists have campaigned for patients with drug‐resistant TB to have access to experimental drugs, particularly one called bedaquiline, before these have been approved by regulatory authorities such as the Food and Drug Administration (FDA) in the United States (US) and the Medicines Control Council (MCC) in South Africa. Some activists have also campaigned for bedaquiline to be approved by regulatory authorities before testing of the drug is completed. These campaigns raise ethical concerns about whether patients should be offered experimental, unapproved, medicines for the treatment of life‐threatening illnesses, and if authorities should approve drugs for life‐threatening illnesses when vital questions about safety and efficacy remain outstanding.